Stomatal patchiness in Mediterranean evergreen sclerophylls Phenomenology and consequences for the interpretation of the midday depression in photosynthesis and transpiration - Beyschlag, Wolfram; Pfanz, Hardy; Ryel, Ronald J.; Botanik, Lehrstuhl; Universitfit, I. I.; Dallenbergweg, Mittlerer; Republic, Federal; Science, Range (Planta, 1992)
Midday depression of net photosynthesis and transpiration in the Mediterranean sclerophylls Arbutus unedo L. and Quercus suber L. occurs with a depression of mesophyll photosynthetic activity as indicated by cal- culated carboxylation efficiency (CE) and constant diur- nal calculated leaf intercellular partial pressure of CO 2 (Ci). This work examines the hypothesis that this midday depression can be explained by the distribution of patches of either wide-open or closed stomata on the leaf surface, independent of a coupling mechanism between stomata and mesophyll that results in a midday depres- sion of photosynthetic activity of the mesophyll. Pressure infiltration of four liquids differing in their surface ten- sion was used as a method to show the occurrence of stomatal patchiness and to determine the status of sto- matal aperture within the patches. Liquids were selected such that the threshold leaf conductance necessary for infiltration through the stomatal pores covered the ex- pected diurnal range of calculated leaf conductance (g) for these species. Infiltration experiments were carried out with leaves of potted plants under simulated Mediterranean summer conditions in a growth chamber. For all four liquids, leaves of both species were found to be fully infiltratable in the morning and in the late after- noon while during the periods leading up to and away from midday the leaves showed a pronounced patchy distribution of infiltratable and non-infiltratable areas. Similar linear relationships between the amount of liquid infiltrated and g (measured by porometry prior to de- tachment and infiltration) for all liquids clearly revealed the existence of pneumatically isolated patches containing only wide-open or closed stomata. The good correspon- dence between the midday depression of CE, calculated * Dedicated to Professor Otto L. Lange on the occasion of his 65th birthday ** To whom correspondence should be addressed Abbreviations: A = net photosynthesis rate; Ci = actual leaf internal CO2 partial pressure; Ci *=apparent leaf internal CO2 partial pressure; CE = actual carboxylation efficiency; CE* = apparent car- boxylation efficiency; E = transpiration rate; g = leaf conductance under the assumption of no stomatal patchiness, and the diurnal changes in non-infiltratable leaf area strongly indicates that the apparent reduction in mesophyll activ- ity results from assuming no stomatal patchiness. It is suggested that simultaneous responses of stomata and mesophyll activity reported for other species may also be attributed to the occurrence of stomatal patchiness. In Quercus coccifera L., where the lack of constant diurnal calculated C i and major depression of measured CE at noontime indicates different stomatal behavior, non- linear and dissimilar relationships between g and the infiltratable quantities of the four liquids were found. This indicates a wide distribution of stomatal aperture on the leaf surface rather than only wide-open or closed stomata.
Keywords: arbutus; Mediterranean; Quercus; Sclerophyll; stomate (control-patchiness)